Production of Bokashi and Liquid Organic Fertilizer (LOF) with Trichoderma Sp. Decomposer Based on Agricultural Waste and Its Application to Horticultural Plants - Maulidi, Maulidi; Warganda, Warganda; Listiawati, Agustina; Asnawati, Asnawati; Indrawati, Urai Suci Yulies Vitri (Universitas Lambung Mangkurat, 2024)
Horticulture farmers in Rasau Jaya 2 Village, Kubu Raya Regency, cultivate plants on peatlands using large amounts of inorganic fertilizers. Continuous use degrades the peat soil and drastically reduces its organic matter content. This reduction leads to soil hardening, poor water flow, and impaired root development, causing decreased horticultural production. Using liquid organic fertilizer (LOF) and organic matter applications is recommended to address these issues. The PKM (Community Service Program) was implemented through lectures, discussions, training, and demonstrations on making bokashi and LOF with Trichoderma sp. decomposer and their application to horticultural plants. Additionally, monitoring and evaluation of PKM activities were conducted in Rasau Jaya 2 Village. This activity's achieved targets and outcomes include farmers' independence in utilizing agricultural waste as raw materials to produce bokashi and LOF, reducing inorganic fertilizer use. Horticulture farmers were highly enthusiastic about the materials for making bokashi and LOF.